Gut microbiota and myeloproliferative neoplasms - Adeniyi Abraham Adesola; Yongfeng Chen; Mihnea Alexandru Gaman (Journal of the Pakistan Medical Association, 2023)
The human gut microbiota refers to the collective assembly of microorganisms inhabiting and colonizing the gastrointestinal tract, including bacteria, archaea, and eukarya.1 This intricate microbial ecosystem exists in a symbiotic relationship with the host, with trillions of microorganisms playing key roles in maintaining human health.2 Firmicutes and Bacteroidetes represent the predominant bacterial phyla that form the intestinal microbiome.2 The gut microbiota has developed adaptive mechanisms to promote its survival within the gastrointestinal tract. Development of the intestinal microbiome has been depicted and seems to be influenced by a variety of factors, e.g., mode of delivery, diet during infancy and adulthood, illnesses, and antibiotic treatment causing variation in the composition of the microbiota.3 Before the age of three, children’s intestinal microbiome already resembles the gut microbiota of adult individuals in terms of functional capabilities, diversity, and composition.4 The gut microbiota offers numerous benefits to the host as its metabolic activity is responsible for the generation of short-chain fatty acids which are a source of energy for the host, and for the fermentation of carbohydrates leading to the synthesis of oxalates, reducing the risk of oxalate stones in the kidney.5 In addition, the microbiota promotes lipid metabolism, vitamin synthesis, polyphenol breakdown, drug metabolism, immunomodulation, which offers immune-protection, and maintains the structural integrity of the gastrointestinal tract.3 Therefore, the gut microbiota represents an intricate microbial ecosystem that plays a critical role in maintaining human health. Continue...